Hubungan Antara Vulva Hygiene Dan Penggunaan Alat Kontrasepsi Dalam Rahim dengan Keputihan pada Wanita Usia Subur - Petri Damiani Anindyajati; Ade Dharmawan; Nicolas Layanto; Monica Cherlady (Jurnal MedScientiae, 2023)
Pathological vaginal discharge is an abnormal disorder that often occurs in women of childbearing age and is characterized by a white discharge with a thick, white-yellow or white-greenish consistency, sometimes accompanied by an unpleasant odor and itching, often caused by several problems such as vulvovaginal infections. This happens because the composition of the vaginal microflora changes, which is influenced by internal factors (age, hormonal changes during menarche, menstruation, and pregnancy) and external factors (hygiene practices, sexual relations, and contraceptive use). The purpose of this article is to look at the relationship between vulva hygiene and intrauterine contraceptives with the incidence of vaginal discharge in women of childbearing age. The data was searched using Google Scholar and PubMed and found 8 articles that met the criteria. Various risk factors that affect the occurrence of vaginal discharge due to the use of non-hormonal intrauterine contraceptive devices that occur in women of childbearing age and through good vulvar hygiene behavior, can reduce the risk of physiological and pathological vaginal discharge. Based on the analysis conducted, it was concluded that there is a relationship between vulva hygiene and the use of intrauterine contraceptive devices with vaginal discharge in women of childbearing age